2009
DOI: 10.1017/s0029665109001025
|View full text |Cite
|
Sign up to set email alerts
|

Session 3: Joint Nutrition Society and Irish Nutrition and Dietetic Institute Symposium on ‘Nutrition and autoimmune disease’ Nutrition in Crohn's disease

Abstract: The exact aetiology of Crohn's disease remains unknown. The consensus is that the disease results from a complex interaction between genes, immunity and environmental factors. Diet is attractive, in theory, as an environmental risk factor in the aetiology of the disease. The epidemiological data, often impeded by methodological issues, have failed to confirm a direct link between pre-diet illness and the development of Crohn's disease. Once diagnosed, however, nutrition has an important role in disease managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 82 publications
0
8
0
1
Order By: Relevance
“…Studies have suggested that Vitamin D status plays an important role in the initiation, progression and/or severity of different autoimmune diseases such as rheumatoid arthritis, multiple sclerosis, asthma, systemic lupus erythematous and inflammatory bowel disease (IBD) [ 2 , 124 , 125 , 126 , 127 , 128 , 129 , 130 ]. IBD such as Crohn’s disease and ulcerative colitis, are chronic, idiopathic inflammatory disorders of the gastrointestinal tract [ 131 ].…”
Section: Implications For Human Diseasementioning
confidence: 99%
“…Studies have suggested that Vitamin D status plays an important role in the initiation, progression and/or severity of different autoimmune diseases such as rheumatoid arthritis, multiple sclerosis, asthma, systemic lupus erythematous and inflammatory bowel disease (IBD) [ 2 , 124 , 125 , 126 , 127 , 128 , 129 , 130 ]. IBD such as Crohn’s disease and ulcerative colitis, are chronic, idiopathic inflammatory disorders of the gastrointestinal tract [ 131 ].…”
Section: Implications For Human Diseasementioning
confidence: 99%
“…Weight loss and malnutrition are well-documented features of CD, affecting an estimated 80% of patients during acute flare-ups and hospital admissions [3][4][5] and are associated with higher mortality, 3 longer hospital stays and higher health care costs. 4 Paradoxically, overweight is now emerging as a further nutritional issue affecting people with CD.…”
Section: Introductionmentioning
confidence: 99%
“…Micronutrient deficiencies are essentially explained by the reduced dietary intake and the underlying malabsorption. They have been associated with prolonged hospitalization and higher mortality [69].…”
Section: Disease Specific Deficiencymentioning
confidence: 99%